Large heterozygous deletion and uniparental disomy masquerading as homozygosity in CHKB gene - Tenghui Wu; Ciliu Zhang; Fang He; Li Yang; Fei Yin; Jing Peng (Molecular Genetics & Genomic Medicine, 2023)
Abstract Background CHKB mutations have been described in 49 patients with megaconial congenital muscular dystrophy, which is a rare autosomal recessive disorder, of which 40 patients showed homozygosity. Methods Peripheral blood genomic DNA samples were extracted from patients and their parents and were tested by whole exome sequencing. Quantitative PCR was performed to detect deletion. Single nucleotide polymorphism analysis was performed to identify uniparental disomy. Quantitative PCR and western blot were used to measure the expression level of CHKB in patient 1‐derived immortalized lymphocytes. Mitochondria were observed in lymphocytes by electron microscopy. Results Two unrelated cases born to non‐consanguineous parents were diagnosed with megaconial congenital muscular dystrophy due to apparently homozygous mutations (patient 1: c.225‐2A>T; patient 2: c.701C>T) in the CHKB gene using whole exome sequencing. Quantitative PCR revealed that patient 1 had a large deletion encompassing the CHKB gene, inherited from the mother. Single nucleotide polymorphism analysis revealed patient 2 had paternal uniparental isodisomy containing the CHKB gene. In the immortalized lymphocytes from patient 1, decreased expression of CHKB was revealed by quantitative PCR and western blot, and giant mitochondria were observed using electron microscopy. Conclusion We provide a possibility to detect giant mitochondria in other cells when muscle was not available. Moreover, clinicians should be aware that homozygous variants can be masqueraded by uniparental disomy or large deletions in offspring of non‐consanguineous parents, and excessive homozygosity may be misdiagnosed.